PUPPET MEDIA IN IMPROVING EARLY CHILDREN'S SPEAKING ABILITIES - yusra yusra (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2023)
It is very important to encourage the development of speech from an early age, because it is one of the most essential aspects of development. This research was conducted at Putroe Nahrisyah Kindergarten, Lhokseumawe City, this is because researchers found problems in group B children that children's speaking skills have not developed, this can be proven that children do not have the confidence to communicate, are quiet, less active, rarely express ideas and lack of interaction between teachers and children during the learning process. This study aims to improve the speaking ability of children aged five to six years through the application of puppet media. This study was conducted on 10 students consisting of six boys and four girls. This study is a classroom action research conducted in two cycles using observation sheets and documentation. The results of the study from cycle I showed that the percentage for Developing As Expected and Developing Very Well was 60%, while in cycle II there was an increase in the percentage value of Developing As Expected and Developing Very Well which was 80%, this proves that puppet media is able to improve children's speaking skills. The implications of this study are expected to be a reference in developing various aspects of early childhood abilities.